Assessment of some physicochemical properties of soil and plants along discharged effluent drainage in Sharada Industrial Area, Kano, Nigeria - SANI A; DARMA AI; RUQAYYA AA (Innovare Journal of Sciences, 2019)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Soil is a vital resource of sustaining basic human needs, a quality food, food supply and a live able environment. Vegetables are vital to the human diet, and in particular provide the well-known trace elements and heavy metals. intake of heavy metal-contaminated vegetables may pose a risk to the human health. Soil and Plants (vegetables) samples were collected from the study sites (A, B, C). They were subjected to heavy metals analysis which includes Cadmium (Cd), Chromium (Cr), Copper (Cu), Lead (Pb) and some physicochemical properties which include pH, Electric conductivity (EC) and Cation Exchange Capacity (CEC) in soil. The mean values of the heavy metals in soil were higher than the recommended value by USDA (2007), while the value recorded at the control site is found to be within the range. <span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The values of Cd, Cr and Pb were lower than <span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">WHO/FAO (1996)<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">safe limit. However, the Cu levels found in vegetables were within safe limits in all samples. The pH and CEC of the three sites are within the range according to USDA (2007). The CEC value of site A and B fall within the range.<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The EC value of site A is higher than site B while site C has the least. These indicate that there is possible interference from the effluent discharged on the soil chemistry.